The Confinement Profile Effect on the Optical Properties in Different Inverse-shaped Single InGaN/GaN Quantum Wells - En-nadir, Redouane; El Ghazi, Haddou; Belaid , Walid; Abboudi, Hassan; Jabouti, Fath allah; Jorio, Anouar; Zorkani, Izeddine (Iraqi Journal of Physics, 2022)
In this work, the effects of size, and temperature on the linear and nonlinear optical properties in InGaN/GaN inverse parabolic and triangular quantum wells (IPQW and ITQW) for different concentrations at the well center were theoretically investigated. The indium concentrations at the barriers were fixed to be always xmax = 0.2. The energy levels and their associated wave functions are computed within the effective mass approximation. The expressions of optical properties are obtained analytically by using the compact density-matrix approach. The linear, nonlinear, and total absorption coefficients depending on the In concentrations at the well center are investigated as a function of the incident photon energy for different values of temperature and quantum wells size. The results show that the In concentrations, size and temperature have a significant effect on these optical properties. The positions of the resonance peaks of the absorption coefficients were blue-shifted under increasing indium compositions in the quantum wells (InGaN) and temperature while they were red-shifted with the increase in the thickness of the wells. Moreover, the amplitudes of the resonance peaks were enhanced under the increase of the In composition, the temperature, and the thickness of the quantum wells. The optical absorption in ITQW structure is slightly greater than that in IPQW one.